Reforming the financing of the European Union: A proposal - Clemens Fuest; Friedrich Heinemann; Martin Ungerer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
In this paper we propose a reform of the EU financing system. The two most important elements of our proposal are i) to make the contribution of taxpayers to the EU budget more visible by showing an EU VAT share on receipts and ii) to increase the power of the European Parliament in the determination of the structure of EU expenditures by limiting the multiannual financial framework to the overall size of the EU budget while the structure of expenditures will be determined annually. It is the objective of the second reform element to give greater weight to policies with EU wide benefits and to crowd back the influence of 'juste retour' thinking on EU expenditures. The setup of this paper is as follows. In section 2 we briefly summarize the current structure of EU revenues and expenditures. Section 3 discusses the critique of the current system and perspectives for reform. In section 4, we present our reform proposal and section 5 concludes.
Keywords: 330